Hyperhomocysteinemia in Takayasu arteritis—genetically defined or burden of the proinflammatory state? - Zarur, Eduarda Bonelli; Peron Filho, Faustino; de Oliveira, Allan Chiaratti; Keppeke, Gerson Dierley; D’Almeida, Vânia; Silva de Souza, Alexandre Wagner (Frontiers in Immunology, 2025)
Takayasu arteritis (TAK) is associated with high plasma homocysteine (Hcy) and elevated Hcy predicts ischemic events. Thus, this study aims to compare the frequency of single-nucleotide polymorphisms (SNPs) of genes involved in Hcy metabolism between TAK and controls and analyze associations with Hcy levels, TAK features, and acute ischemic arterial events (AIAEs). A cross-sectional study was performed with 73 TAK patients and 71 controls. SNPs of genes involved in the Hcy metabolism, plasma Hcy, and risk factors were analyzed for hyperhomocysteinemia (HHcy), cardiovascular disease (CVD), and AIAEs. Patients presented a higher frequency of risk factors for CVD and HHcy. At least one AIAE was observed in 27 (37.0%) patients and one control. The frequency of the SNPs was similar between both groups, and there was no association between SNP carriage and AIAEs. TAK patients presented higher Hcy levels than controls (13.9 ± 5.6 µmol/L vs. 8.6 ± 4.0 µmol/L; p < 0.001), and patients carrying MTHFR677TT presented higher Hcy levels than those carrying MTHFR677CT (20.4 ± 7.8 µmol/L vs. 13.7 ± 5.2 µmol/L; p = 0.02) or MTHFR677CC (20.4 ± 7.8 µmol/L vs. 13.1 ± 4.7 µmol/L; p = 0.009). TAK was an independent risk factor for HHcy [odds ratio (OR) = 10.20; 95% confidence interval (95% CI): 4.16–25.00; p < 0.001], and in TAK, thiazide diuretic use was a risk factor for HHcy (OR = 11.61; 95% CI: 1.63–82.63; p < 0.01). In conclusion, TAK was a risk factor for HHcy but not related to SNPs in genes encoding Hcy metabolism enzymes. The burden of chronic inflammation and thiazide diuretics contribute to HHcy in TAK.